The Impact of Body Mass Index and Some Trace Elements in Iraqi Women with Breast Cancer - Rana K. Al-Saady (مجلة كلية الطب, 2016)
Background: Breast cancer is a highly heterogeneous disease globally. Trace elements such as copper and zinc have a role in many biochemical reactions as micro source, their metabolism is profoundly altered in neoplastic diseases especially breast cancer which is ranked as the first of female cancers Objective: The aim of the present study is to study the impact of body mass index and some trace elements in Iraqi women with breast cancer. Patients and methods: The group of the study consisted of 25 breast cancer patients; their age range was (25–65) years recruited from the Al-Kadhimia Teaching Hospital and 25 apparently healthy women age matched, over a period of 6 months from January 2015 until June 2015. After the diagnosis was made using a histopathological examination for the malignant tumor, blood was obtained from all patients and control, centrifuged and serum samples without blood hemolysis were separated and stored at – 20 until assayed. Results: There was a significant increase in body mass index in breast cancer women as compared to control group. Copper and zinc levels were significantly different between the patients and controls group with higher level of copper, zinc. Also copper/zinc ratio in patients was higher than in the control group. Conclusions: The excess copper and zinc in breast cancer women in comparison to healthy control highlights the role of these trace elements in the initiation or promotion of breast cancer. It is recommended to use trace elements and the copper/zinc ratio as biomarkers for breast cancer disease and its progression.